MPEG-I Immersive Audio: A Versatile and Efficient Representation of VR/AR Audio Beyond Point Source Rendering - Herre, Jürgen; Disch, Sascha; Borss, Christian; Silzle, Andreas; Adami, Alexander; Peters, Nils (2024 6th International Conference on Audio for Games, 2024)
The emerging MPEG-I Immersive Audio Standard for Virtual Reality and Augmented Reality (VR/AR) Audio provides a wide range of capabilities for 6DoF rendering of virtual scenes from simple point source rendering to sophisticated modelling of acoustic sources (object, channel and HOA sources with extent, directivity and Doppler), and environmental aspects (early reflections, late reverberation, occlusion and diffraction). Furthermore, the scene representation metadata is compressed into a compact bitstream that is ideal for streaming and storage. Waveform carriage of acoustic sources relies on MPEG-H audio. This paper describes the general architecture of the standard and highlights some of its advanced features. The Final Draft International Standard (FDIS) of the specification is scheduled for January 2025.
herre_papers_virtual_and_augmented_reality_rendering